An Analysis Of Students’ Strategy In Learning Simple Past Tense At Eighth Grade Of SMP Negeri 21 Palembang - Inton Inton; Dewi Kusmiati; Masagus Firdaus (Journal of Innovative and Creativity, 2025)
This research examines for students studying English as a second language, mastering grammar—especially the simple past tense—is crucial. Nonetheless, a lot of students still struggle to write and speak in the past tense accurately. The purpose of this study is to examine how SMP 21 Palembang eighth-grade students acquire the simple past tense. This research employed a descriptive qualitative method supported by quantitative data. The participants were 28 students from class VIII in the 2024/2025 academic year. Data were collected through questionnaires, classroom observations, and interviews. The results revealed that students applied three major types of strategies: cognitive strategies (memorizing verbs and practicing exercises), metacognitive strategies (planning and evaluating their learning), and social strategies (asking for help from teachers or peers). Cognitive strategies were the most dominant (53.6%), followed by social strategies (28.6%), and metacognitive strategies (17.8%). The results show that students' comprehension of the simple past tense was improved when they combined these tactics. The findings indicate that most students rely on repetition and memorization rather than contextual understanding, suggesting the need for more communicative and meaningful grammar instruction.